2013
DOI: 10.1017/s2040174413000287
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine environment and cognitive development in young twins

Abstract: Intrauterine factors important for cognitive development, such as birth weight, chorionicity and umbilical cord characteristics were investigated. A total of 663 twin pairs completed the Wechsler Intelligence Scale for Children-Revised and scores were available for Performance, Verbal and Total Intelligence Quotient (IQ). The intrauterine factors examined were birth weight, placental weight and morphology, cord knots, cord length and cord insertion. IQ scores for the varying levels of the intrauterine markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
(101 reference statements)
0
11
0
Order By: Relevance
“…No differences on 6 McCarthy scales. Antoniou et al ( 2010 ) 663 twin pairs Belgium Examination of placenta 7–15 years, M = 10.4 years MZ versus DZ on placentation Bivariate ACE models BWT-IQ and cord knots-IQ associations No chorionicity effect Spitz et al ( 1996 ) 20 MZMC 24 MZDC 24 DZ France Ultrasound and macroscopic examination at delivery 8–12 years MZMC versus MZDC Intra-class correlations Anthropometric measures at birth and assessment; Cognitive battery (Vocabulary, block design from WISC-R, K-ABC, perception and mental rotation r MC < r DC for BWT, child weight, height, BMI. r MC > r DC block design.…”
Section: Resultsmentioning
confidence: 99%
“…No differences on 6 McCarthy scales. Antoniou et al ( 2010 ) 663 twin pairs Belgium Examination of placenta 7–15 years, M = 10.4 years MZ versus DZ on placentation Bivariate ACE models BWT-IQ and cord knots-IQ associations No chorionicity effect Spitz et al ( 1996 ) 20 MZMC 24 MZDC 24 DZ France Ultrasound and macroscopic examination at delivery 8–12 years MZMC versus MZDC Intra-class correlations Anthropometric measures at birth and assessment; Cognitive battery (Vocabulary, block design from WISC-R, K-ABC, perception and mental rotation r MC < r DC for BWT, child weight, height, BMI. r MC > r DC block design.…”
Section: Resultsmentioning
confidence: 99%
“…The East Flanders Prospective Twin Survey (EFPTS) is a population based register of multiple births in the province of East-Flanders (Belgium) since 1964 [15]. 376 twin pairs born between 1982 and 1992 were invited, in 1992 and between 1996 and 1999 child IQ was assessed with use of the WISC-R (Wechsler Intelligence Scale for Children-Revised) test [16, 17]. The parents filled out the Child Behaviour Checklist (CBCL) [16].…”
Section: Methodsmentioning
confidence: 99%
“…Although twins display significant deficits in early cognitive ability, it is also established that they catch up to the population mean by early childhood (Antoniou et al, 2013;Ross et al, 2012), making rapid gains in standardized cognitive scores across the toddler years (Wilson, 1974(Wilson, , 1975. Wilson (1974) concluded that the recovery to the population mean was most pronounced between ages 4 and 6 years, observing mean Wechsler Preschool & Primary Scale of Intelligence (WPPSI) Full Scale IQ (FSIQ) scores of 92.6, 95.9, and 100.9 at ages 4, 5, and 6 years, respectively.…”
Section: Patterns Of Cognitive Development: Early Childhood Through A...mentioning
confidence: 99%